Intercultural Latin American Research on Abuse in Couple Relationships of Young University [Investigación Intercultural Latinoamericana Sobre Maltrato en Las Relaciones de Pareja de Jóvenes Universitarios] - Morales-Navarro, M (Sociedad Interamericana de Psicologia, 2021)
Courtship, dating or crush is a romantic experience, of linking, commitment and support, among the members in a couple, on the framework of a cultural context. in the framework of a social context, which contributes to psychosocial well-being and has relevance in the socio-emotional development of people. However, during this period, many couples face situations of violence. The aim was to analyze and to describe the presence, type and level of abuse in a Courtship, dating or crush in three Latin American countries. Method, 1017 students aged 17 to 30 years, university students aged 17 to 30 years from Argentina, Chile and Mexico participated. The Dating Abuse Questionnaire (CMN; Osorio-Guzmán, 2014), which contains 5 areas and α = 0.95, was applied. The study met the ethical standards of the American Psychological Association. Results, the proportion of participants was Argentina (26.9%), Chile (29.7%) and México (43.4%). The general reliability of the instrument ranges from .93 to .95. It was found that more than 90% of the cases report low levels of abuse, women report greater severity and 22.6% reported family violence patterns. Conclusions, the naturalization of violence in courtship and the mutuality of courtship is confirmed. © 2021, Sociedad Interamericana de Psicologia. All rights reserved.